1999
DOI: 10.1046/j.1365-3083.1999.00607.x
|View full text |Cite
|
Sign up to set email alerts
|

Participation of CD1 Molecules in the Presentation of Bacterial Protein Antigens in Humans

Abstract: Human CD1 molecules, expressed on the surface of professional antigen-presenting cells (including dendritic cells, Langerhans' cells, B cells and activated monocytes) are structurally homologous to major histocompatibility complex (MHC) class I and class II molecules. CD1b and CD1c have been shown to present nonpeptide bacterial antigens to T cells. We hypothesized that CD1 molecules may also be involved in the presentation of bacterial protein antigens. Human peripheral blood mononuclear cells (PBMC) were exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 24 publications
1
4
0
Order By: Relevance
“…The essential role of renal CD1d in SEB-associated pathogenesis was further validated with a fluorescence-based assay demonstrating the sequential inhibition of CD1d and preventing its binding to SEB (Figure 5 ). In agreement, multiple studies observed diminished host defense as a result of the targeted CD1d deficiency [ 37 , 40 , 59 , 60 ]. It was, however, beyond the scope of the present study to suggest putative SEB-induced toxemia through CD1d-independent routes.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…The essential role of renal CD1d in SEB-associated pathogenesis was further validated with a fluorescence-based assay demonstrating the sequential inhibition of CD1d and preventing its binding to SEB (Figure 5 ). In agreement, multiple studies observed diminished host defense as a result of the targeted CD1d deficiency [ 37 , 40 , 59 , 60 ]. It was, however, beyond the scope of the present study to suggest putative SEB-induced toxemia through CD1d-independent routes.…”
Section: Discussionsupporting
confidence: 77%
“…The involvement of CD1d in pathogenesis has been investigated in the past, primarily focused on the lymphoid cells [ 37 - 41 ], while the knowledge gap exists in comprehending the CD1d-mediated pathogenesis in kidney cells and its role in the late stage of pathogenesis. To bridge the knowledge gap, our study sought to understand the renal response to SEB shock, focusing on the interaction of SEB with CD1d in RPTECs.…”
Section: Introductionmentioning
confidence: 99%
“…In order to analyse the nature of ex vivo effector cells, 1 × 10 6 PBMC were incubated with 10 µ g/ml of anti‐CD56 (Leu‐19, Becton Dickinson), anti‐CD16 (clone 3G8, IgG1, Immunotech) [26] or 1 µ g/ml of anti‐TCR γδ (Pan γ/δ , clone IMM 510, Immunotech) MoAb. Target cells were incubated with 10 µ g/ml of anticlass‐I MHC (anti‐HLA‐ABC, IgG2 κ (mouse), clone B9·12·1, Immunotech), anticlass‐II MHC (anti‐HLA‐DR, IgG2a, clone L243, Becton Dickinson) or anti‐CD1b (anti‐CD1b, IgG2a, clone 4.A7·6, Immunotech) [27] MoAb. After 1 h‐incubation at 37°C, effector and target cells were washed twice and used in the cytotoxic assay.…”
Section: Methodsmentioning
confidence: 99%
“…Presentation of protein antigens by CD1 molecules, such as tetanus toxoid (TT), has also been reported [8]. Specific upregulation of CD1a, CD1b and CD1c on circulating monocytes in vitro as well as in vivo by TT has also been shown, suggesting a role for CD1 molecules in the immune response to TT [9].…”
Section: Cd1 Function and Inductionmentioning
confidence: 96%